LNG as Marine Fuel under LGF Code: A Meta-Analysis of Emission Reduction, Economic Viability and Safety Performance - Yusuf Pria Utama; Rini Setiyawati; Rizal Rochmansyah; Nurul Wahyuni H.; Fitri Mulyana (Dinasti International Journal of Digital Business Management, 2026)
The International Maritime Organization's (IMO) decarbonization targets necessitate adopting alternative fuels. Liquefied Natural Gas (LNG), regulated by the International Code of Safety for Ships Using Gases or Other Low-Flashpoint Fuels (IGF Code), offers potential emission reductions but faces debates regarding methane slip and cost-effectiveness. This meta-analysis synthesized 48 peer-reviewed studies (2015–2024) following PRISMA guidelines. Random- effects models quantified LNG’s performance versus conventional fuels (HFO/MDO) in emissions (CO₂eq, SOₓ, NOₓ, PM), economics (CAPEX/OPEX), and safety. Heterogeneity was assessed via I² statistics. LNG reduces SOₓ by 98% (95% CI: 96–99), NOₓ by 25% (18–32), and PM by 93% (88–97). Net CO₂eq reduction is 12% (5–19) after methane slip adjustment (0.2–5%). CAPEX is 25% higher (SMD = 1.8; 1.5–2.1), but OPEX is 22% lower (SMD = -1.2; -1.8 to -0.6). Safety incidents are 1.8× more likely (OR = 1.8; 1.2–2.7), mitigated by IGF-compliant training (OR = 0.6; 0.4–0.9). LNG achieves immediate air quality benefits but requires methane slip abatement for climate goals. Policy priorities include bio-LNG blending and global bunkering standardization